ANALISIS MODEL PEMBELAJARAN KOOPERATIF DALAM MENINGKATKAN MINAT BACA SISWA SDN 01 BENGKAYANG - Naina Kristina (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
The research in this article aims to increase students' interest in reading at SDN 01 Bengkayang in Indonesian language subjects when implementing the learning process in class. This researcher also aims to explore whether the application of the cooperative learning model can stimulate students' interest in learning to be enthusiastic about participating in the learning process. As we have seen together, the interest in reading at SDN 01 Bengkayang students is still very minimal and this can have an impact on other students, therefore there is a need for guidance from adults, especially from parents, so that they can educate their children more routinely. Reading is one of the learning activities that is very important to help students achieve applied competencies, understand each material in learning, apart from that, reading can also help students to obtain information. Therefore, students must be able to develop an interest in reading by diligently opening books, even if only for a moment. Therefore, students must be able to manage their time for reading so that their interest in reading increases and students don't have to spend the whole day but can also use free time to practice reading, this is the first step to growing students' interest in reading.